2015
DOI: 10.3389/fpls.2015.01088
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Expression Profiling of Rice Tetraspanin Genes Reveals Diverse Roles During Development and Abiotic Stress

Abstract: Tetraspanin family is comprised of evolutionarily conserved integral membrane proteins. The incredible ability of tetraspanins to form ‘micro domain complexes’ and their preferential targeting to membranes emphasizes their active association with signal recognition and communication with neighboring cells, thus acting as key modulators of signaling cascades. In animals, tetraspanins are associated with multitude of cellular processes. Unlike animals, the biological relevance of tetraspanins in plants has not b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…AtTET10 and OsTET14 from O . sativa can be considered the founders of the tetraspanin family in their respective species [35, 50]. We identified 13 putative tetraspanin sequences in P .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AtTET10 and OsTET14 from O . sativa can be considered the founders of the tetraspanin family in their respective species [35, 50]. We identified 13 putative tetraspanin sequences in P .…”
Section: Resultsmentioning
confidence: 99%
“…vulgaris , 25 in Glycine max , 9 in Medicago truncatula , and 5 in Lotus japonicus (Fig 1 and S2 Fig). Seventeen tetraspanins have been described in the model plant Arabidopsis and 15 in Oryza sativa [35, 50]. PvTET10, and other orthologs of AtTET10 and OsTET14, have between 10 and 12 introns in all reported genomes, including Marchantia polymorpha and Physcomitrella patens .…”
Section: Resultsmentioning
confidence: 99%
“…A 2501-bp promoter sequence of OsGRX20 gene from Xiushui 11 was identical with that from Yongjing 50A. In this sequence, several putative cis -elements associated with stress responses including heat shock element, low temperature response element ( Mani et al, 2015 ), MYB binding site ( Smita et al, 2015 ), dehydration-responsive element ( Maruyama et al, 2012 ) and W-box ( Smita et al, 2015 ), were identified by using the PlantCARE and PLACE databases. Consistently, the transcript levels of OsGRX20 significantly responded to Xoo attack, MeV, heat, cold, salt, and PEG-6000 treatments in our expression studies ( Figure 3 and Supplementary Figure S2A ).…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, the transcript levels of OsGRX20 significantly responded to Xoo attack, MeV, heat, cold, salt, and PEG-6000 treatments in our expression studies ( Figure 3 and Supplementary Figure S2A ). The hormone-responsive elements were also identified in the promoter region of OsGRX20 gene: ABREs or ABA-responsive elements ( Maruyama et al, 2012 ), TGACG- or CGTCA-motif responsible for JA-responsiveness ( Mani et al, 2015 ), AuxRE for auxin response ( Smita et al, 2015 ), TCA-element for the response to SA and pathogen infection ( Mou et al, 2013 ). Furthermore we found that OsGRX20 transcript showed a significant increase in response to exogenous application of SA, JA, ABA, and 2,4-D (Supplementary Figure S2B ).…”
Section: Discussionmentioning
confidence: 99%
“…In Oryza sativa 15 TET genes have been annotated, which Mani et al (2015) have recently begun to functionally characterize. Their analysis of rice microarray datasets and spatial-temporal expression profiles indicated that similar to AtTETs OsTETs display variable and partially overlapping expression patterns and are regulated by abiotic stresses, leaf senescence, nutrient deprivation and hormones.…”
Section: Tet Expression In Ricementioning
confidence: 99%